(untitled) (Journal of the College of Education for Women, 2019)
Altruism is one of good qualities of human being expressing his highness and triumph. Self control has A signifies in a lot of psychological, educational, Social, ethical and healing fields Where the higher self control relates with high degrees of carefulness accuracy, problem solving, choice. judgment and decision making. the present study aimos at measuring altruism among university students , self control among them , recognizing the statistically differences significance on self control among university students according to gender variable and recognizing the correlation between attruism and self control among university students . the sample consists of the basic application one (200) students (100) males and (100) males that had been chosen randomly. the researcher reaches toThe following results:1- The individuals of the sample_ Baghdad university Students and AL-Mustansyriha university ones according the comparison between arithmetic mean and hypothetical one-characterized with altruism at (0,05) Significance level.2-The individuals of the sample Baghdad university students and AL-Mustansyriha university ones- according to the Comparison beteen arithmetic mean and hypothetical one- Characterized with the ability of self control at (0,05) Significance level.3-There are no statistical significance level on altruism scale according to type variable (males- females) at (0,05) significance level.4- There are statistical significance level on self control scale according to type variable (males- females ) at (0,05) significance level.5-There is a correlation between altruism and self control (0,74) among the students of both universities at (0,05) significance level.The researcher reaches to number of suggestion recommendation and conclusions.